Menjaga Kemandirian di Tengah Penurunan Fisik: Dinamika Kehidupan Lansia di Panti Werdha Harapan Ibu - Dian Nurul Laili; Melinda Aprilia Nurul Wafa; Muhammad Feyzal Rizkillah; Aulia Intan Lutfiyana; Aulia Sabila Rahmadani; Shafira Khoirunnisa Ramadhani; Zalfaa Auliya Khonsa; Naumy Maulidiya Amanda; Keyla Noandri Az Zahra; Siti Hikmah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The elderly stage is characterized by complex physical, psychological, and social changes, often leading to a decline in bodily functions and limitations in daily activities. This condition frequently results in older adults becoming highly dependent on assistance from others, including family members and caregivers in nursing homes. This study aims to understand the changes in bodily functions experienced by older adults and to identify factors that accelerate or worsen these processes, particularly among those residing in nursing homes. The research employed a descriptive qualitative approach, involving three older adult participants and one caregiver at Harapan Ibu Nursing Home. Data were collected through in-depth interviews and analyzed descriptively to illustrate patterns of functional decline and influencing factors. The main findings indicate that older adults experience decreased mobility, muscle strength, motor function, as well as impairments in vision and hearing. However, those who remain active in daily activities and receive environmental support demonstrate better levels of independence and quality of life. The study concludes that the decline in bodily functions among older adults is a natural process that can be slowed through physical activity, social support, and a supportive environment, enabling them to maintain a meaningful and independent life despite limitations.